Elaboration of Mathematical Content on Social Site: A Pedagogical Approach for Contemporary and Future Learning of Mathematics - Singh, Jayveer (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
We need present good elaboration of mathematical content in our educational institution and social site (as; Facebook, twitter telegram, edmodo and social blogs etc). We need to reduce fear of mathematics and anxiety of mathematics. Elaboration of mathematical concept on social-site as a better way of learning. Blended approaches of learning are capable for reducing fear of mathematics, and their difficulty. elaboration of mathematics on social sites are enable to reduce their ―difficulty‖, ―anxiety‖ and ―math phobia‖. Good way of elaboration of mathematics, and create learner behaviour ―Joy‖. elaboration of mathematics on social-sites are direct the new way of thinking and constructing and also provide new way of transforming mathematical knowledge. Effective elaboration of mathematics are required good understanding mathematics in respect to content and good understanding of mathematics pedagogy in respect to ―what learners know and how learners know‖. The feedback of the document and researches are ―learner need dropping to teaching and educating and apply new approaches of transforming knowledge as facilitating and elaborating. Elaboration of mathematics on social site as educational technological tools are focused on the learner understanding in world-wide context. Elaboration of mathematics on social site are provided a new blended approach of transforming mathematical knowledge. Elaboration of mathematics on social site are provided infinite resource of learning in front of learners (as Students, Teachers, Researchers, Educators, etc). Elaboration of mathematics on social site are provided a philosophical (epistemological) view of mathematics learning. Elaboration of mathematics on social site and its applications are beneficial for the regular and non-regular usergers of social site. In a wold-wide view younger learners are expending more time surfing social site. Therefore elaboration of mathematics on social site is a best way of  enriching mathematics knowledge and its understanding.In this paper the researcher is Discuss about the elaboration of mathematics on social sites as a new way of transforming of mathematics learning. Because at present and in future blended learning approach is more convenient and more effective for the learner.